Ultrasonic characterization of binary mixture of 2, 3-dichloroaniline and polyethylene glycols. (October 2021) - Kumar, Mahendra; Khan, Mohd Aftab; Yadav, Chandreshvar Prasad; Pandey, Dharmendra Kumar; Singh, Dhananjay
Highlights: Ultrasonic Characterization of binary mixture of 2, 3- Dichloroaniline with PEGs. Measurement of density, viscosity and ultrasonic velocity at 27 °C and 1 atm. Estimation of mole fraction dependent thermo-physical properties. Characteristic determination based on elastic, thermal and ultrasonic parameters. Explanation of molecular interaction, stability and structural ordering. Abstract: The present study is focused on the ultrasonic characterization of binary mixture having constituent liquids 2, 3-dichloroaniline as solute and polyethylene glycols (PEGs) with average molecular weight 200, 400 and 600 as solvent by measurement of density, viscosity, ultrasonic velocity and estimation of thermo-physical parameters at 27 °C and atmospheric pressure 100.3 kPa. The density and acoustic impedance are received to decay while viscosity, ultrasonic velocity, adiabatic compressibility, free length, internal pressure, thermal relaxation time, Gibbs free energy and ultrasonic absorption are found to enhance with an increase in mole fraction of solvents in synthesized binary mixtures The analysis of measured and estimated parameters reveal that the molecular interaction, structural ordering and stability of binary mixture shall enhance with increase in molar mass/mole fraction of PEGs. The ultrasonic absorption is found to be predominantly affected by viscosity. The present study is useful in chemical/pharmaceutical industries and further investigation.